The Role of the Microenvironment – Models for the Study of Melanoma - Speroni, Lucia; Bustuoabad, Victoria de los Angeles; Gasparri, Julieta; Chiaramoni, Nadia Silvia; Alonso, Silvia del Valle (IntechOpen, 2011)
None